Brief information related to potential therapeutic tendencies of citrus plants - Asif, Mohammad (International Journal of Biological Research, 2014)
Citrus plants play an important role as a health-protector. They are containing various phytochemical that reduce or prevent risk for various diseases such as cancer, heart disease and aging effects. Citrus are good sources of naturally occurring antioxidants like vitamin C, vitamin E, carotenes, phenolic acids, phytate and phytoestrogens that have been recognized potentially to reduce various disease risks. Some compounds, have strong antioxidant activity, while others, such as the mono-phenols are weak antioxidants. Antioxidant compounds scavenge free radicals and thus inhibit the oxidative mechanisms that lead to degenerative diseases. The free radicals may oxidize nucleic acids, proteins, lipids or DNA and can initiate degenerative disease. There are a number of studies suggesting that the antioxidants are the main factors for reducing the incidence of chronic diseases including heart disease and some cancers. Keywords: Citrus, Antioxidants, Vitamins, Degenerative Diseases.